Hybrid Method for Topology Optimization Based on a Meta-Heuristic Method and Pixel Connectivity - Ruzbehi, Shabnam; Hahn, Ingo (IET-PEMD, 2020)
One of the recent developments in engineering optimization is the topology optimization. This method is common in mechanical engineering and optimization of mechanical structures, but it can be used to design novel structures of the electromagnetic devices and electrical machines. In general, topology optimization results need a further development or post-processing to gain a device, which is more adapted to the manufacturing process. Therefore, a hybrid optimization method is offered, which is based on a meta-heuristic method like the Genetic Algorithm (GA). Because of irregular shapes of the optimized topologies, a local method, called pixel connectivity technique, is presented to regularize the structure in a two-level optimization with a focus on the improvement of the meta-heuristic method via GA and post-processing inspired by an image processing method. The Finite Element Method is used to analyse a well-known E-core actuator developed by applying the proposed topology optimization method as a case study. The optimization goal is to achieve the greatest savings of material and gain a lighter weight of the device, while preserving the electromagnetic force at an appropriate level. It is possible to extend and apply this proposed method to different active components of electrical machines in combination with other goals.<br
Keywords: TOPOLGY OPTIMIZATION; PIXEL CONNECTIVITY; REGULARIZATION METHOD; BINARY METHOD; HYBRID METHOD.